2HDM neutral scalars under the LHC - Felix Kling; Shufang Su; Wei Su (Journal of High Energy Physics, 2020)
Abstract Two Higgs Doublet Models (2HDM) provide a simple framework for new physics models with an extended Higgs sector. The current LHC results, including both direct searches for additional non-Standard Model (SM) Higgs bosons, as well as precision measurements of the SM-like Higgs couplings, already provide strong constraints on the 2HDM parameter spaces. In this paper, we examine those constraints for the neutral scalars in the Type-I and Type-II 2HDM. In addition to the direct search channels with SM final states: H/A → f f ¯ $$ f\overline{f} $$ , VV, Vh, hh, we study in particular the exotic decay channels of H/A → AZ/HZ once there is a mass hierarchy between the non-SM Higgses. We found that H/A → AZ/H Z channel has unique sensitivity to the alignment limit region which remains unconstrained by conventional searches and Higgs precision measurements. This mode also extends the reach at intermediate t β for heavy m A that are not covered by the other direct searches.